2017
DOI: 10.1021/acs.analchem.7b00817
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Protonated Sulfone and Aromatic Carboxylic Acid Functionalities in Organic Molecules by Using Ion–Molecule Reactions Followed by Collisionally Activated Dissociation in a Linear Quadrupole Ion Trap Mass Spectrometer

Abstract: Gas-phase reactivity of protonated model compounds with different functional groups toward trimethoxymethylsilane (TMMS) was studied to explore the utility of this reagent in mass spectrometric identification of specific functionalities for potentially rapid characterization of drug metabolites. Only protonated analytes with a carboxylic acid, a sulfone, or a sulfonamide functionality formed diagnostic adducts that had lost a methanol molecule upon reactions with TMMS. Collisionally activated dissociation (CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 26 publications
5
42
0
Order By: Relevance
“…Reaction of lipid ions with hydrogen atoms and radical oxygen species resulted in formation of metastable lipid radical ions revealing DB positions and snisomer abundances upon activation. In other experiments, Kenttämaa and co-workers have shown that BF 3 or trimethoxymethylsilane can track the presence of adjacent functional groups in glucuronide [98] or sulfone/carboxylic acid/sulfonamide [99] groups after ion/molecule reactions, respectively. For example, Niyonsaba et al investigated negatively charged drugs ion/molecule reaction mass spectrometry.…”
Section: Ion/molecule and Ion/ion Reactionsmentioning
confidence: 97%
“…Reaction of lipid ions with hydrogen atoms and radical oxygen species resulted in formation of metastable lipid radical ions revealing DB positions and snisomer abundances upon activation. In other experiments, Kenttämaa and co-workers have shown that BF 3 or trimethoxymethylsilane can track the presence of adjacent functional groups in glucuronide [98] or sulfone/carboxylic acid/sulfonamide [99] groups after ion/molecule reactions, respectively. For example, Niyonsaba et al investigated negatively charged drugs ion/molecule reaction mass spectrometry.…”
Section: Ion/molecule and Ion/ion Reactionsmentioning
confidence: 97%
“…Previously, the proton affinity (PA) of an analyte was used to predict whether the protonated analyte would undergo diagnostic product formation or proton transfer or if there is no reaction. 28,29 These proton affinity values were then compared to that of MOP to hypothesize whether a diagnostic product ion would be formed over no reaction or proton transfer from the protonated analyte to MOP. 8 If the PA of the analyte is lower than that of MOP, proton transfer usually dominates.…”
Section: Figurementioning
confidence: 99%
“…8−10 Furthermore, it may also complicate the identification of functional groups in protonated analytes via functional-group selective gas-phase ion−molecule reactions as different protomers may exhibit different reactivities. 11,12 In this context, extensive research has been carried out to better understand the influence of solvents and other variables on the protonation sites of 4-aminobenzoic acid upon electrospray ionization (ESI) in tandem mass spectrometry. 2,6,13−15 When 4-aminobenzoic acid is protonated on the amino nitrogen, the charge is localized on the amino group, which facilitates solvation in the liquid phase.…”
Section: ■ Introductionmentioning
confidence: 99%